Reassessing the radical Enlightenment - Ducheyne, Steffen, Ed (Routledge, 2017)
"Reassessing the Radical Enlightenment' comprises fifteen new essays by a team of international scholars that re-evaluate the characteristics, meaning and impact of the radical Enlightenment"--Provided by publisher.